An overview of mechanisms, biomarkers, and treatment strategies for acquired anti-EGFR resistance in RAS wild-type colorectal cancer - Ding, Chenxiang; Yao, Ruoyu; Wang, Yong; Liu, Hongjie; Li, Chunyan; Xie, Hua (Frontiers in Pharmacology, 2025)
Colorectal cancer (CRC) is a threat to public health, with a global incidence and mortality of over 1.9 million and 0.9 million people, respectively. Anti-epidermal growth factor receptor (EGFR)-based treatment is recommended for CRC with wild-type rat sarcoma (RAS). However, after continuous treatment with this regimen, acquired resistance occurs, which hampers the prognosis of patients. The median progression-free survival of patients with metastatic CRC receiving first-line anti-EGFR-based treatment is 10–13 months. The widely recognized mechanisms that induce acquired anti-EGFR resistance are related to the activation of the RAS/RAF/MEK/ERK and PI3K/AKT/mTOR signaling pathways. In addition, novel mechanisms that induce acquired resistance, such as microsatellite stability/mismatch repair status, noncoding RNAs, the tumor microenvironment, exosome-mediated intracellular communication, and post-transcriptional modification, are being discovered. To improve personalized medication, biomarkers with predictive value for acquired anti-EGFR resistance are recognized from both tumoral samples and liquid biopsies. On the basis of the identified mechanisms, clinicians have developed several treatment strategies to cope with acquired anti-EGFR resistance. This review provides an overview of acquired anti-EGFR resistance in RAS wild-type CRC by summarizing the common genes and proteins, potential novel mechanisms, and predictive biomarkers related to acquired anti-EGFR resistance, as well as treatment strategies to address this resistance. This review may serve as a potential reference for exploring possible treatment strategies for acquired anti-EGFR resistance.